ChemInform Abstract: Reusable and Removable Directing Groups for C(sp2)—H Bond Functionalization of Arenes. Issue 44 (15th October 2015) - Yadav, M. Ramu; Rit, Raja K.; Shankar, Majji; Sahoo, Akhila K.
Abstract Review: [58 refs.